Corneal Sensation and Nerve Fiber Changes in Patients With Interstitial Cystitis - (:unkn) unknown (My University, 2021)
PURPOSE: Central sensitization syndromes are associated with ocular surface discomfort and certain changes in corneal sensation. The aim of this study was to evaluate corneal changes in patients with interstitial cystitis (IC). METHODS: Thirty patients with IC and 32 healthy control subjects were included in this study. All patients had a detailed ophthalmological examination including measurement of corneal sensation with Cochet-Bonnet esthesiometer, tear breakup time, Schirmer I test, and Ocular Surface Disease Index questionnaire. After these examinations, corneal subbasal nerve plexus of the patients was evaluated with in vivo corneal confocal microscopy (IVCM) and the images were analyzed using fully automated software (ACC Metrics Corneal Nerve Fiber Analyzer V.2). RESULTS: There was no significant difference between the groups regarding age and gender distribution. Corneal sensation was significantly higher in patients with IC (P = 0.03), whereas tear breakup time, Schirmer I test, and Ocular Surface Disease Index scores were similar between the patients and controls. IVCM demonstrated nerve fiber loss in patients with IC. Corneal nerve fiber density, corneal nerve branch density, and corneal nerve fiber length were significantly reduced in patients with IC compared with healthy controls (P < 0.001, P = 0.04, and P < 0.001, respectively). CONCLUSIONS: Patients with IC had increased corneal sensation and decreased nerve fiber density in IVCM analysis. Corneal nerve fiber loss might decrease the induction threshold of the remaining fibers to induce peripheral sensitization, which may also trigger central sensitization in long term.